Intraosseous Mucoepidermoid Carcinoma in the Mandible. (17th December 2018) - de Freitas, George Borja; de França, Arthur José Barbosa; dos Santos, Stefanny Torres; de Lima Júnior, Miqueias Oliveira; da Fonte Neto, Adilis Stepple; Bernardon, Paula
Abstract : Although it is a rare neoplasm, intraosseous mucoepidermoid carcinoma is the most common and well-recognized intraosseous salivary gland tumor. Usually, it presents as an asymptomatic volume increase and most patients perceive the presence of the lesion within a year or less of evolution. They are more common in middle-aged adults and have a slight female predilection. They are three times more common in the mandible than in the maxilla and are most often found in the area of the molars and mandibular ramus. The most frequently present symptom is cortical bulging, although some lesions may be discovered as an accidental finding on radiographs. The main modality of treatment for patients with this neoplasm is radical surgical resection, offering a greater chance of cure than the more conservative procedures, such as enucleation or curettage, due to the great possibility of recurrence and tumor metastasis. This paper reports a rare case of intraosseous mucoepidermoid carcinoma occasionally discovered after panoramic radiography of the jaws, which was treated with segmental resection through hemimandibulectomy.